Children's narrative coherence in 'Achieving Best Evidence' forensic interviews and courtroom testimony. Issue 2 (7th February 2023) - VanMeter, Faith; Henderson, Hayden; Konovalov, Hailey; Karni-Visel, Yael; Blasbalg, Uri
ABSTRACT: In the United Kingdom, Section 27 of the Youth Justice and Criminal Evidence Act permits 'Achieving Best Evidence' (ABE) forensic interviews to replace the evidence-in-chief in cases involving children. It is therefore imperative that forensic interviewers elicit complete, reliable, and coherent narratives from children. The goal of the current research study was to assess the coherence of forensic interviews and whether the interviewers' emotional or cognitive support was associated with increases in the coherence of these interviews. Children's narrative coherence was examined in 80 transcripts of ABE investigative interviews with 7- to-15-year-olds who disclosed sexual abuse. Narrative coherence was assessed using the Narrative Coherence Coding Scheme, including three dimensions of narrative coherence: chronology, consistency, and theme (Reese, E., Haden, C. A., Baker-Ward, L., Bauer, P., Fivush, R., & Ornstein, P. A. (2011). Coherence of personal narratives across the lifespan: A multidimensional model and coding method. Journal of Cognition and Development, 12 (4), 424–462. https://doi.org/10.1080/15248372.2011.587854). Findings revealed that first elicited events were more likely to be more coherent compared to subsequently elicited events, and child engagement was positively associated with all dimensions of narrative coherence. Interviewer support was positively associated with chronology, script accounts of abuse were associated with decreased consistency and chronology (but not theme), and cognitive support was not associated with any dimension of narrative coherence.